A New Environmental Governance - Zorondo-Rodriguez, F (Springer International Publishing, 2019)
At present, there is no unified theoretical framework to deal with environmental governance issues. Consequently, there is a diversity of interpretations of the concept at the public-political arena both nationally and internationally. Recent Latin American efforts have given a step forward conceptualizing environmental governance from the South and systematizing experiences to illustrate a diverse contemporaneous reality. At a regional scale, within the last decades, discursive turns in national policies such as the introduction of the sustainable development concept have triggered an increase in studies and applications of environmental governance (e.g., forest s governance, climate change, marine coastal zones) including the use of the ecosystem services concept. The instrumentation of public actions in relation to environmental governance derives from the states. However, if analyzed with a beyond-the-States view, governance can be understood as a process involving the participation of governmental and non-governmental actors reaching decisions, for mutual benefits, through negotiation processes. However, there is not, still, within the countries of the region, inclusive and participative governance oriented toward the sustainable use of natural resources. Although there are many challenges, in this chapter we discuss two of them: (1) to build an analytical framework to understand the environmental governance modes currently available in Latin America and (2) to generate a new sociopolitical interdisciplinary framework involving both natural and sociopolitical systems as a contribution to a new analytical framework for environmental governance. In other words, new environmental governance for Latin America. © Springer Nature Switzerland AG 2019. All rights reserved.